1993
DOI: 10.1111/j.1558-5646.1993.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

A LIFE‐HISTORY BASED STUDY OF POPULATION GENETIC STRUCTURE: SEED BANK TO ADULTS IN PLANTAGO LANCEOLATA

Abstract: Abstract. -We explored the extent to which the soil seed bank differed genetically and spatially in comparison to two actively growingstages in a natural population of Plantago lanceolata. All seedbank seeds, seedlings,and adults of P. lanceolata within eight subunits in a larger population were mapped, subjected to starch gelelectrophoresis, and allozyme analysis in 1988. Gel electrophoresis was also used to estimate the mating system in two years, 1986 and 1988. The spatial distributions of seeds, seedlings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
117
5
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 35 publications
9
117
5
1
Order By: Relevance
“…sibship were individually ground and wicks stored at Ϫ80ЊC. Maternal and seedling samples were subject to starch gel electrophoresis in 1992 and 1994, respectively, using protocols described in Tonsor et al (1993). Five polymorphic loci (number of alleles) were resolved: mdh1 (2), mdh2 (3), got1 (3), got2 (3), and 6pgd (3).…”
Section: Outcrossing Ratementioning
confidence: 99%
“…sibship were individually ground and wicks stored at Ϫ80ЊC. Maternal and seedling samples were subject to starch gel electrophoresis in 1992 and 1994, respectively, using protocols described in Tonsor et al (1993). Five polymorphic loci (number of alleles) were resolved: mdh1 (2), mdh2 (3), got1 (3), got2 (3), and 6pgd (3).…”
Section: Outcrossing Ratementioning
confidence: 99%
“…[14]. Secondly, it could be attributed to a temporal Wahlund effect [14], but see [20]. Thirdly, Vitalis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Despite their effort, scientists have been unable to conclusively confirm such a role of seed banks in evolutionary dynamics of plant populations [9], [11][17]. While some authors have demonstrated differences between seed banks and aboveground populations such as higher genetic diversity of seed bank populations [9], [13], higher heterozygosity of aboveground populations [11][15] or significant differences in allele frequencies [11], [12], [14], [15], studies of others show no differences in any of the population genetic parameters investigated [16], [17]. This discrepancy stems partly from different methodological approaches to comparing genetic diversity parameters of seed banks with the parameters of different stages of aboveground populations (i.e., seedlings or adults, or combination of both).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WHILE ECOLOGICAL STUDIES OF EPIPHYTIC VASCULAR PLANTS have continued along the lines of classic descriptive studies (Went 1940, Johansson 1974, those focusing on ecological processes and population dynamics have become more common, including studies on factors affecting seedling recruitment and establishment (Ackerman et al 1996, Callaway et al 2002, Jacquemyn et al 2007, spatial distribution (Tremblay 1997, Zotz & Vollrath 2002, Otero et al 2007, Jacquemyn et al 2009), demography (Tonsor et al 1993, Hietz 1997, Kalisz et al 2001, Zotz et al 2005, Janeèková et al 2006, Zotz & Schmidt 2006, evolution of pollination strategies (Ackerman 1986), and genetic structure of the population (Tremblay & Ackerman 2001, Trapnell et al 2004, Trapnell & Hamrick 2006.…”
mentioning
confidence: 99%